2019
DOI: 10.5222/jarss.2019.39306
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Peripheral Block Methods For Position Pain in Femoral Neck Fractures

Abstract: Kalça kırığı gibi ortopedik patolojiler yaşlı popülasyonda sıklıkla görülmektedir. Hasta sayısındaki artış yüzünden, kalça kırığı nedeni ile tedavi gören hastalarda ağrı yönetimi daha önemli hale gelmektedir. Biz bu çalışmada, spinal anestezi için verilen pozisyon sırasındaki ağrıyı gidermek için kullanılan, 2 farklı periferik blok yöntemini, etkinlik ve hasta memnuniyeti açısından karşılaştırdık. Yöntem: Çalışmamız tek merkezli, prospektif, randomize, çift kör bir çalışma olarak planlandı. Her biri 60 yaşın ü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Two studies reported the incidence rate of nausea and vomiting, 15 , 18 while 3 studies reported the incidence rate of sedation. 14 , 21 , 26 Significant heterogeneity was not found in all included studies; therefore, a fixed-model was used ( P > .05). Compared with FICB, FNB significantly reduced the incidence rates of nausea, vomiting, and sedation (relative rate: .30, 95% CI: .12-.79, P = .01) (relative risk: .13, 95% CI: .02-.71, P = .02) (relative risk: .40, 95% CI: .20-.81, P = .01; Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies reported the incidence rate of nausea and vomiting, 15 , 18 while 3 studies reported the incidence rate of sedation. 14 , 21 , 26 Significant heterogeneity was not found in all included studies; therefore, a fixed-model was used ( P > .05). Compared with FICB, FNB significantly reduced the incidence rates of nausea, vomiting, and sedation (relative rate: .30, 95% CI: .12-.79, P = .01) (relative risk: .13, 95% CI: .02-.71, P = .02) (relative risk: .40, 95% CI: .20-.81, P = .01; Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…This may limit the ability to distinguish between block types using these interventions. Third, the placement of block or timing of block placement varied among the included trials: the ultrasound-guided placement was applied in less than half of the trials, 13 , 15 , 17 , 19 , 22 , 26 and the timing of placement was only recorded in 4 trials. 13 , 14 , 20 , 22 Ultrasound guidance is a superior technique for visualizing the anatomical structures during the administration of nerve blocks and can be used to confirm the correct placement of FNB and FICB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations